The Paradox of Planning in World War II - Hugh Rockoff (Rutgers University, Department of Economics, 1996)
According to the standard accounts of the mobilization of resources in the United States during WWII, things went badly in the beginning because the agencies in charge were given insufficient authority and were mismanaged. But then in 1943 the story continues, the War Production Board installed the famous Controlled Materials Plan which solved the major problems and turned disaster into triumph. A reexamination of the Plan in the light of information on munitions production, however, reveals that the Plan was too little and too late to account for the success of the mobilization. One implication is that pecuniary incentives may have played a larger role than has been recognized.
Keywords: N1; N4; 330; Controls; World War II